Effect of coulomb confinement resonances on time delay in Ne@C60-5. (August 2015) - Kumar, Ashish; Varma, H R; Deshmukh, P C; Manson, S T; Dolmatov, V K; Kheifets, A S
Synopsis: Wigner time delay for inner and outer shells of Ne@C60 -5 have been studied using relativistic random phase approximation (RRPA) [1]. Coulomb confinement resonances (CCR) due to the charged nature of fullerene cause prominent effects on the photoionization time delay of 1s subshell. These CCRs in 1s also results in significant modifications of the time delay in 2s and 2p ionization channels through interchannel coupling at energies far above their thresholds.